Characterisation techniques for analysis of imidazolium-based ionic liquids and application in polymer preparation: a review - Noorhisham, Nur Athirah; Amri, Deana; Mohamed, Ahmad Husaini; Yahaya, Noorfatimah; Ahmad, Nor Monica; Mohamad, Sharifah; Kamaruzaman, Sazlinda; Osman, Hasnah (Elsevier, 2021)
Over the past decades, imidazolium-based ionic liquids (ILs) have been studied extensively in numerous previous experimental and analysis works to produce ILs with tunable physicochemical properties. Imidazolium-based ILs is one of the most studied ionic liquid in the literature, and the number of published papers related to ILs have also been rising exponentially. It can be used in polymer synthesis due to its intrinsically low viscosity, low melting points, simplicity of preparation, and high stability toward oxidative and reductive conditions. However, very limited information on characterisation of imidazolium-based ILs was available in the literature. Thus, this paper provides a comprehensive review of the characterisation analysis of imidazolium-based ILs. The characterisation of imidazolium-based ILs via spectrochemical methods (FTIR, 1H and 13C NMR, and UV-Vis), CHNSO elemental analysis, thermal stability analysis (TGA and DSC) and crystallinity analysis using XRD were thoroughly discussed herein. Moreover, this review also presents the cutting-edge-knowledge of different synthesis method of imidazolium-based ILs and its potential applications in polymer preparation.